2006
DOI: 10.1007/bf03194594
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-culture-responsive and autotetraploidy-responsive changes in metabolic profiles of cucumber (Cucumis sativus L.)

Abstract: Somaclonal variation commonly occurs during in vitro plant regeneration and may introduce unintended changes in numerous plant characters. In order to assess the range of tissue-culture-responsive changes on the biochemical level, the metabolic profiles of diploid and tetraploid cucumber R1 plants regenerated from leaf-derived callus were determined. Gas chromatography and mass spectrometry were used for monitoring of 48 metabolites and many significant changes were found in metabolic profiles of these plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Despite the presence of duplicated genes in tetraploids it may not cause duplicated transcription and translation and duplicated enzyme activity. Several works have shown variable effects of genome dosage on the production of metabolites . In accord with this information, cultivars of the same species do not contain the same amount of antioxidants, what was showed, for example, in twelve cultivars of wheat treated with low UV‐B dose .…”
Section: Discussionmentioning
confidence: 66%
“…Despite the presence of duplicated genes in tetraploids it may not cause duplicated transcription and translation and duplicated enzyme activity. Several works have shown variable effects of genome dosage on the production of metabolites . In accord with this information, cultivars of the same species do not contain the same amount of antioxidants, what was showed, for example, in twelve cultivars of wheat treated with low UV‐B dose .…”
Section: Discussionmentioning
confidence: 66%
“…The tetraploid Lycopersicum esculentum showed a diverse enzymatic response to polyploidization, i.e., malate dehydrogenase, acid invertase and acid phosphatase activity increased, while peroxidase activity decreased and neutral phosphatase and esterase concentrations were not affected (reviewed in [ 53 ]). In a metabolic comparison between tetraploid lines generated from the diploid Cucumis sativus L., Filipecki et al [ 56 ] concluded that differences in metabolic profiles were tissue-culture responsive and did not correlate directly with the range of genome changes in tetraploids. We note here that while all of the above studies have made a valuable contribution to understanding the effects of gene dosage, these studies were targeted to specific metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…cepa [9], A . fistulosum [10], Solanum tuberosum [11], Cucumis sativus L. [12] and Agapanthus praecox [13] but also in the model dicotyledonous plant Arabidopsis thaliana [14]. Considerable changes in the global DNA methylation levels as well as methylation at specific sites have been demonstrated for tissue cultures of oil palm [15], grapevine [16] and apple [17].…”
Section: Introductionmentioning
confidence: 99%